Management of Heart Failure in Patients with Chronic Kidney Disease - David K Ryan; Debasish Banerjee; Fadi Jouhra (European Cardiology Review)
Chronic kidney disease (CKD) is increasingly prevalent in patients with heart failure (HF) and HF is one of the leading causes of hospitalisation, morbidity and mortality in patients with impaired renal function. Currently, there is strong evidence to support the symptomatic and prognostic benefits of β-blockers, renin–angiotensin–aldosterone inhibitors (RAASis), angiotensin receptor-neprilysin inhibitors (ARNIs) and mineralocorticoid receptor antagonists (MRA) in patients with HF and CKD stages 1–3. However, ARNIs, RAASis and MRAs are often suboptimally prescribed for patients with CKD owing to concerns about hyperkalaemia and worsening renal function. There is growing evidence for the use of sodium–glucose co-transporter 2 inhibitors and IV iron therapy in the management of HF in patients with CKD. However, few studies have included patients with CKD stages 4–5 and patients receiving dialysis, limiting the assessment of the safety and efficacy of these therapies in advanced CKD. Interdisciplinary input from HF and renal specialists is required to provide integrated care for the growing number of patients with HF and CKD.